Greek islands 2025 - Ver Berkmoes, Ryan; Averbuck, Alexis, 1972-; Iatrou, Helen; Maric, Vesna, 1976-; Schulte-Peevers, Andrea (Lonely Planet, 2025)
Lonely Planet's 'Greek Islands' is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Roam through Rhodes' Old Town, explore Nisyros Volcano, and indulge in Crete's fresh food; all with your trusted travel companion. Get to the heart of the Greek Islands and begin your journey now!